1984
DOI: 10.1042/bst0120887
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cytochemistry: a precise form of cellular biochemistry

Abstract: Origins of quantitative cytochemistry It is recorded (Needham & Baldwin, 1949, p. 245), that almost 100 years ago, a distinguished organic chemist tried to divert Gowland Hopkins' interest in biochemistry : 'The chemistry of the living? That is the chemistry of protoplasm; that is superchemistry; seek, my young friend, for other ambitions'. This attitude was related to the concept that the chemistry of the whole, or of the cell or of protoplasm was likely to be greater than the sum of its parts, and to the old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It is envisioned that the wider application of the rigorous and quantitative cytochemical techniques developed by Chayen and co-workers to the intricate and rapidly changing micro-environment of the developing limb will be a powerful tool allowing precise dissection of specific changes in cell behaviour, at a time when phenotypic cellular complexity is being established. 33 …”
Section: The Role Of Mapk Signalling In Controlling Behaviour Of the mentioning
confidence: 99%
“…It is envisioned that the wider application of the rigorous and quantitative cytochemical techniques developed by Chayen and co-workers to the intricate and rapidly changing micro-environment of the developing limb will be a powerful tool allowing precise dissection of specific changes in cell behaviour, at a time when phenotypic cellular complexity is being established. 33 …”
Section: The Role Of Mapk Signalling In Controlling Behaviour Of the mentioning
confidence: 99%
“…Cellular biochemistry or quantitative in situ biochemistry, coupled with scanning and integrating microdensitometry, has been developed as a quantitative procedure to achieve these aims (Chayen and Bitensky, 1992;Chayen, 1984). Using such a quantitative assay for UDPGD activity (Mehdizadeh et al, 1991), it was shown that UDPGD activitykell in intimal fibroblast-like synoviocytes was six or more times higher than in cells in the synovial subintima (Pitsillides et al, 1993).…”
Section: Ukmentioning
confidence: 99%
“…Quantitation of a cytochemical reaction product within individual cells is well recognized as a sensitive method for measurement of enzyme activity and of hormonal action in cryostat sections of tissues (Chayen, 1984). In this study, dispersed cultured cells were used, and absorbances were measured in standard areas of cytoplasm.…”
Section: Discussionmentioning
confidence: 99%